Nitrogen Management for Teff Hay Production - D. H. Min; J. L. Moyer (Kansas Agricultural Experiment Station Research Reports, 2016)
Fertilization of teff with the ESN source of nitrogen (N) at the higher rates, 100 and 125 lb N/a resulted in increased seasonal forage production. The primary increase occurred in the second of three cuttings.
Keywords: pastures; hay